Analytical solution for twinning deformation effect of pre-strained shape memory effect beam-columns. (August 2019) - Ostadrahimi, Alireza; Taheri-Behrooz, Fathollah
In this article, an analytical solution is presented for twinning deformation effect of a prismatic shape memory alloy beam-column. To this end, a reduced one-dimensional Souza model is employed to study the bending stress of a pre-strained shape memory alloy beam-column at low temperatures. Analytical expressions for bending stress as well as polynomial approximations for deflection are obtained. Derived equations for bending problem are employed to analyze twinning deformation effect of shape memory alloy beam-columns with rectangular and circular cross sections. Furthermore, the distance of zero-stress fiber from the center line during loading is studied. The results of this work show good agreement when compared with experimental data and finite element results.